Multimodal imaging of small hard retinal drusen in young healthy adults. Issue 1 (19th October 2017) - Pedersen, Hilde R; Gilson, Stuart J; Dubra, Alfredo; Munch, Inger Christine; Larsen, Michael; Baraas, Rigmor C
Abstract : Background: Small hard macular drusen can be observed in the retina of adults as young as 18 years of age. Here, we seek to describe the in vivo topography and geometry of these drusen. Methods: Retinal images were acquired in young, healthy adults using colour fundus photography, spectral domain optic coherence tomography (SD-OCT), reflectance flood-illuminated adaptive optic ophthalmoscopy (AO flood) and reflectance adaptive optic scanning light ophthalmoscopy (AOSLO) in both confocal and non-confocal split-detection modalities. Small bright yellow hard drusen within a 10 degree radius from the foveal centre were characterised. Results: Small hard drusen were seen on colour photographs in 21 out of 97 participants and 26 drusen in 12 eyes in 11 participants were imaged using the full protocol. Drusen were easily identifiable in all modalities, except a few very small ones, which were not visible on SD-OCT. On AOSLO images, these drusen appeared as round, oval or lobular areas (up to three lobules) of diameter 22–61 µm where cone photoreceptor reflectivity and density was decreased (p=0.049). This was usually associated with discrete thickening of the retinal pigment epithelium (RPE) complex. Conclusion: High lateral resolution imaging of small lobular hard retinal drusen suggests formation through the confluence of two or more smaller round lesions. The outline and size of these smaller lesions corresponds to 1–4 RPE cells. Prospective longitudinal studies are needed to determine the ultimate fate of small hard drusen and their potential relation to age-related macular degeneration.